TECHNICAL-TECHNOLOGICAL AND SOCIAL TECHNIQUES OF FOOD SAFETY PROVISION IN CUSTOMS UNION COUNTRIES - V. A. Alyoshina (Russian Journal of Economics and Law)
Objective: to describe the mechanism of technical-technological and social factors influence on food safety of Customs Union countries. Methods: statistical, analytical, economic-mathematical. Results: Basing on analytical data and expert estimations, the author grounds the technique of designing the profile of food safety of a state enabling to multilaterally characterize the influence of external and internal factors, to make conclusions concerning the dynamics of food safety indicators and to give recommendations on elimination of the revealed negative trends, as well as to determine the integral safety level. Scientific novelty: economic-mathematical methods are applied to specify the food saefety indicators, the technical-technological aspect and social factors determining the food safety of the region are described, the technique of designing and characterizing the economical safety profile is tested on the example of Customs Union countries. Practical value: using the technique for analyzing the state policy efficiency in the sphere of food safety and estimation of the country’s economy preparedness to repell the global crisis influence on the world food markets.